Інструментарій PR у маркетингу сфери В2С - Ткачук (Стахурська), Світлана Валеріївна (My University, 2025)
У статті розглядається інструментарій формування зв’язків з громадськістю у маркетингу сфери В2С (у споживчому маркетингу). Інструменти пропонується розподіляти на дві групи: класичні інструменти та сучасні інструменти. До класичних інструментів віднесено медіа-комунікації, реалізацію корпоративної соціальної відповідальності (CSR), івент-маркетинг та партнерство. У якості сучасних інструментів піар розглядаються диджитал піар, партизанський маркетинг і продакт плейсмент. Кожна група нараховує багато прийомів, методів і різновидів інструментів. Загальний інструментарій піар розглядається як система, де набір класичних і сучасних інструментів тісно взаємодіють, створюючи єдину піар-кампанію бренду. Робиться акцент на формуванні зв’язків з громадськістю в сфері В2С, де, на відміну від промислового маркетингу, доцільними є креативи, амбієнтний маркетинг, вірусний ефект, челленджі та інші прийоми, що покликані створити позитивне ставлення кінцевого споживача до бренду, сформувати довгострокову лояльність та створити нативний зв’язок у свідомості споживача між брендом та сукупністю позитивних емоцій. Запропонована система є доцільною практично для будь-якої сфери В2С, включаючи сферу виробництва та продажу харчових продуктів. The article examines the tools for forming public relations in B2C marketing (consumer marketing). It is proposed to divide the tools into two groups, classical tools and modern tools, which together form a single system of public relations. This system involves a complex set of combinations of modern and classical PR tools in order to form an effective PR strategy and PR campaign in the B2C marketing system. The classic tools include media communications (press releases, press kits, articles, interviews, press conferences), corporate social responsibility (CSR: charity, environmental initiatives, social projects), event marketing and partnerships (participation in exhibitions and fairs, branded events, sponsorship). Modern PR tools include digital PR (SMM, SEO, influencer marketing), guerrilla marketing (ambient, ambush, viral, grassroots, and street marketing), and product placement (visual, verbal, functional, integrated). Each group includes many techniques, methods, and types of tools. The general PR toolkit is seen as a system where a set of classical and modern tools interact closely to create a single brand PR campaign. The emphasis is placed on the formation of public relations in the B2C sphere, where, unlike industrial marketing, creativity, ambitious marketing, viral effect, challenges and other techniques are appropriate, which are designed to create a positive attitude of the end consumer to the brand, form long-term loyalty and create a native connection in the consumer's mind between the brand and a set of positive emotions. Social media marketing is one of the most important coordinated PR tools used in conjunction with other tools. The proposed system is appropriate for almost any B2C area, including the production and sale of food products, catering, consumer goods, etc. The use of the proposed system of PR tools should be systematic, constantly updated and improved, taking into account trends and other factors of the external marketing environment. This is especially true for modern PR tools: guerrilla marketing, social media marketing, and product placement. These tools are most affected by external factors, and achieving a viral effect requires regular updating of ideas, taking into account general current trends and marketing trends.
PR toolkit in B2C marketing
Keywords: піар; PR; зв’язки з громадськістю; інструменти PR; споживчий маркетинг; consumer marketing; кафедра маркетингу; кафедра маркетингу